(untitled) (ARQUISUR Revista, 2018)
This paper gathers analysis and conclusions of two research works on the recent production of social housing in Uruguay and seeks to represent a contribution to the development and decision-making in these programs. The first one compares the physical, social and economic results, when it is carried out with the self-management of the addressees, or hiring companies “key in hand”, that take all the management decisions. The second work analyzes the characteristics, accomplishments, potentialities and obstacles faced by the cooperative system of mutual help, implemented in Uruguay in 1968, that now takes an important impulse. These investigations were developed by an interdisciplinary team from the social, physics and economic areas that - based on the project terms and execution conditions, direct field observation, and information obtained in interviews and meetings with addressees and technicians - analyzing advantages and disadvantages of each model and making recommendations for their use in new proposals. The key conclusion highlights the importance of the participation of the addressees within the project and program management, which significantly improves the results and to consolidate the relationship of belonging with them.